Application of Intelligent Passive Devices Based on Shape Memory Alloys in Seismic Control of Structures. (February 2016) - Asgarian, Behrouz; Salari, Neda; Saadati, Behnam
Abstract: In this study, seismic application of an innovative control device called self-centering hybrid damper (SCHD) is investigated. Two main characteristics of the SCHD result in structural response mitigation. Steel pipe as a vertical link and two transverse pairs of Shape Memory Alloy (SMA) wires are used as energy dissipation and recentering components, respectively. Adjustable design parameters including design load, incorporation percentage of SMA, pipe height and wire inclination angle provide desirable structural responses. A numerical parametric study revealed the effect of each parameter on device performance. Besides, an optimum incorporation percentage of SMA in design load was obtained from the parametric study. The results also indicated that in addition to ideal energy dissipation capability, SCHDs can effectively reduce the permanent displacement. Nonlinear time-history analysis of a 5-story building equipped with the SCHD was conducted to evaluate the effectiveness of the device. The results indicated that utilization of the proposed innovative damper is an effective way in reduction of roof acceleration, peak interstory drift and permanent displacement.